Pembuatan Biochar dan Pupuk Organik Untuk Budidaya Tanaman Anggur pada KWT Mentari Kota Pontianak - Sutikarini Sutikarini; Agusalim Masulili; Donna Youlla (Institut Riset dan Publikasi Indonesia (IRPI), 2023)
Mentari Women Farmers Group (KWT) which was formed in 2019. Grape cultivation in Pontianak City is still new / newbie so that it has obstacles in the partner group in cultivation. Through this activity, the team wishes to build an alternative to partner problems, namely making biochar and organic fertilizer (bokasi), how to make and apply in the form of good planting media for organic cultivation of grape plants. The methods of PKM activities for this group are: 1) preparation stage, 2) training and implementation stage consisting of counseling, pretest and post test, training in making biochar and bokasi organic fertilizer and application in grape cultivation, and 3) evaluation stage. The results of PKM activities show that grape plants have the potential to become the group's superior commodity by utilizing biochar and organic fertilizers derived from waste that is abundant around the group, namely coconut waste and pineapple skin. After the Community Service activities, the Mentari Women Farmers Group of Pontianak City increased both affective (knowledge), cognitive (attitude) and skills in the use of coconut waste as biochar and pineapple peel waste as bokasi organic fertilizer for grape cultivation so that it is expected to increase grape production and income of the partner group.